The Prognostic Impact of Tumor Architecture for Upper Urinary Tract Urothelial Carcinoma: A Propensity Score-Weighted Analysis - Liu, Hui-Ying; Chen, Yen Ta; Huang, Shun-Chen; Wang, Hung-Jen; Cheng, Yuan-Tso; Kang, Chih Hsiung; Lee, Wei Ching; Su, Yu-Li; Huang, Chun-Chieh; Chang, Yin-Lun; Chuang, Yao-Chi; Luo, Hao Lun; et al. (Frontiers in Oncology, 2021)
Purpose To assess the association of tumour architecture with cancer recurrence, metastasis, and cancer-specific survival (CSS) in patients treated with radical nephroureterectomy (RNU) for upper urinary tract urothelial carcinoma (UTUC) in Taiwan. Materials and Methods Data were collected from 857 patients treated with RNU between January 2005 and August 2016 in our hospital. Pathologic slides were reviewed by genitourinary pathologists. Propensity score weighting was performed for data analysis. Results Sessile growth pattern was observed in 212 patients (24.7%). Tumour architecture exhibited a significant association with bladder cancer history, chronic kidney disease (CKD), tumour stage, lymph node status, histological grade, lymphovascular invasion, concomitant carcinoma in situ, and the variant type [SMD > 0.1 for all variables before weighting]. In the propensity score analysis, 424 papillary and sessile tumour architecture were analysed to balance the baseline characteristics between the groups. Tumour architecture was an independent predictor of metastatic disease and CSS (p = 0.033 and p = 0.002, respectively). However, the associations of tumour architecture with bladder and contralateral recurrence were nonsignificant (p = 0.956 and p = 0.844, respectively). Conclusions Tumour architecture of UTUC after RNU is associated with established features of aggressive disease and predictors of metastasis and CSS. Assessment of tumour architecture may help identify patients who could benefit from close follow-up or early administration of systemic therapy after RNU. Tumour architecture should be included in UTUC staging after further confirmation.